(untitled) (Canadian Journal of Counselling and Psychotherapy, 2007)
To provide culturally-sensitive mental health services, clinicians must transcend the culturebound assumptions implicit in traditional theories of counselling and psychotherapy and enter the unique worldviews of their clients. This article will describe two models of counselling and psychotherapy which are based on a synthesis of developmental theory and multicultural counselling theory with a co-constructivist epistemology. Developmental Counselling and Therapy (DCT) provides a culturally centred treatment framework for work with individual clients. Systemic Cognitive-Developmental Therapy (SCDT) extends the developmental framework to work with partners, families, and wider social groupings. Using these two models, the authors present five principles aimed at helping clinicians to expand their own understanding of self and client worldviews and to develop more culturally centred treatment practices.